Differences in the flight initiation distance near expressways and in open farmland in wintering Common Buzzards (Buteo buteo) - P. Cieśluk; Z. Kasprzykowski (The European Zoological Journal)
The development of road networks has given rise to man-made wildlife habitats. Birds of prey use roadsides and highway infrastructure as attractive foraging sites. In order to measure reactions to human disturbance, the flight initiation distance (FID) of Common Buzzards (Buteo buteo) foraging on expressways and in open farmland was investigated. The GLM model showed that FID was affected by habitat types, distance from the nearest building and distance from the nearest tree. Common Buzzards have a shorter FID on expressway than in farmland. The distance from the nearest building and the distance from the nearest tree were positively correlated with FID. Our results confirmed the behavioural plasticity of these birds and may provide a theoretical basis for measures aimed at reducing the risk of collisions with moving road vehicles.